2002
DOI: 10.1136/bmj.324.7334.393
|View full text |Cite
|
Sign up to set email alerts
|

Measles, mumps, and rubella vaccination and bowel problems or developmental regression in children with autism: population study

Abstract: Objectives To investigate whether measles, mumps, and rubella (MMR) vaccination is associated with bowel problems and developmental regression in children with autism, looking for evidence of a "new variant" form of autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
4
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(157 citation statements)
references
References 13 publications
7
142
4
4
Order By: Relevance
“…13 Measles, mumps, and rubella vaccination also has been related to autism, 14 but no evidence for this relationship has been found in several other studies. [15][16][17] Furthermore, it has been suggested that the mercury-based preservatives of vaccines increase the risk for autism, but this hypothesis has met criticism. 18 Intrauterine exposure to teratogenic drugs including thalidomide and valproate may increase the risk for autism.…”
Section: Introductionmentioning
confidence: 99%
“…13 Measles, mumps, and rubella vaccination also has been related to autism, 14 but no evidence for this relationship has been found in several other studies. [15][16][17] Furthermore, it has been suggested that the mercury-based preservatives of vaccines increase the risk for autism, but this hypothesis has met criticism. 18 Intrauterine exposure to teratogenic drugs including thalidomide and valproate may increase the risk for autism.…”
Section: Introductionmentioning
confidence: 99%
“…Among other factors, there was a considerable discussion about the occurrence of autism by immunization with the measles, mumps, and rubella vaccines. However, further careful examination of the data found no association with autism (Dales et al 2001;Taylor et al 2002). Therefore, they are no longer considered to be environmental risk factors.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Kagan-Kushnir et al (20) found an increased incidence of reflux and diarrhea in children with autism compared wth nonaffected siblings. Taylor et al (21) reported significant gastrointestinal problems in children with autism, apparently more likely in the regressive type. These gastrointestinal problems were not more frequent in the group who received MMR than those in the group who did not receive MMR before its introduction in 1988.…”
Section: Part One: the Measles-mumps-rubella Debatementioning
confidence: 99%